What Did Jesus Promise? - Haidle, Helen; Nang Chan Yeema (New York. USA Multnomah Publishers, Inc., 1999)
Presents sixteen selections from the Bible containing promises which Jesus spoke concerning forgiveness, prayer, giving, and heaven.
Keywords: Juvenile Nonfiction